Naphthoquinone as a New Chemical Scaffold for Leishmanicidal Inhibitors of Leishmania GSK-3 - Victor Sebastián-Pérez; Paula Martínez de Iturrate; Montserrat Nácher-Vázquez; Luis Nóvoa; Concepción Pérez; Nuria E. Campillo; Carmen Gil; Luis Rivas (Biomedicines, 2022)
More than 1 billion people live in areas endemic for leishmaniasis, which is a relevant threat for public health worldwide. Due to the inadequate treatments, there is an urgent need to develop novel alternative drugs and to validate new targets to fight this disease. One appealing approach is the selective inhibition of protein kinases (PKs), enzymes involved in a wide range of processes along the life cycle of Leishmania. Several PKs, including glycogen synthase kinase 3 (GSK-3), have been validated as essential for this parasite by genetic or pharmacological methods. Recently, novel chemical scaffolds have been uncovered as Leishmania GSK-3 inhibitors with antiparasitic activity. In order to find new inhibitors of this enzyme, a virtual screening of our in-house chemical library was carried out on the structure of the Leishmania GSK-3. The virtual hits identified were experimentally assayed both for leishmanicidal activity and for in vitro inhibition of the enzyme. The best hits have a quinone scaffold. Their optimization through a medicinal chemistry approach led to a set of new compounds, provided a frame to establish biochemical and antiparasitic structure–activity relationships, and delivered molecules with an improved selectivity index. Altogether, this study paves the way for a systemic search of this class of inhibitors for further development as potential leishmanicidal drugs.